Using a virtual environment to study child pedestrian behaviours: a comparison of parents' expectations and children's street crossing behaviour. Issue 5 (30th March 2015) - Morrongiello, Barbara A; Corbett, Michael
Abstract : Objective: The aim of this study was to compare parents' expectations for their children crossing streets with children's actual crossing behaviours and determine how accurately parents judge their own children's pedestrian behaviours to be. Method: Using a fully immersive virtual reality system interfaced with a 3D movement measurement system, younger (7–9 years) and older (10–12 years) children's crossing behaviours were assessed. The parent viewed the same traffic conditions and indicated if their child would cross and how successful she/he expected the child would be when doing so. Results: Comparing children's performance with what their parents expected they would do revealed that parents significantly overestimated the inter-vehicle gap threshold of their children, erroneously assuming that children would show safer pedestrian behaviours and select larger inter-vehicle gaps to cross into than they actually did; there were no effects of child age or sex. Child and parent scores were not correlated and a logistic regression indicated these were independent of one another. Conclusions: Parents were not accurate in estimating the traffic conditions under which their children would try and cross the street. If parents are not adequately supervising when children cross streets, they may be placing their children at risk of pedestrian injury because they are assuming their children will select larger (safer) inter-vehicle gaps when crossing than children actually do.